Implikasi Hukum Penggunaan Senjata Kimia (Chemical Weapons) Dalam Perang Suriah Menurut Hukum Humaniter Internasional - Homol Prima Sitompul Sitompul (Fakultas Hukum Universitas Mulawarman, 2019)
The case of the use of chemical weapons in the Syrian war raises a concern for the international world in the effort to maintain world peace. The use of chemical weapons is a crime and also a violation of humanitarian law. This is because Syria does not heed humanitarian law as a cornerstone of rules in terms of war. Material and immaterial losses must be immediately accounted for due to the use of chemical weapons in the war. Here is needed how the real law enforcement to resolve violations of humanitarian law, and also the responsibilityof Syria to the victims so that cases like this can not be repeated again. This research aims to find out and analyze humanitarian law such as what was violated by Syria, and find solutions to legal settlement to provide certainty and accountability to victims in the war that occurred in Syria.